A comparative study on the efficacy of isotonic and hypotonic intranasal corticosteroid spray in allergic rhinitis - Ghani, Nik Mohd Syukra Nik Abdul (2017)
Background: Intranasal corticosteroid spray is one of the most effective treatment in allergic rhinitis. There are various types of intranasal corticosteroid spray available in Malaysia. Although the main ingredient in nasal spray is steroid-based products, the difference of tonicity could show different effect in controlling the symptoms of allergic rhinitis. Tonicity is an important consideration for drug formulation and can affect its uptake, retention and consequent efficacy and safety. Objective: This comparison study is to determine the efficacy of different type of nasal spray in treatment of allergic rhinitis by comparing the efficacy using several clinical parameters that are Total Nasal Symptom Score (TNSS), Sinonasal Outcome Test Score-22 (SNOT-22) and Modified Lund-Kennedy (MLK) nasoendoscopic examination. Efficacy is also determined with allergy inflammatory markers such as serum Interleukin-4 and blood eosinophilic count. Methods: Comparative interventional study, open label involving 2 groups (hypotonic nasal spray group and isotonic nasal spray group) was carried out in Otorhinolaryngology Clinic of Hospital Sultanah Nur Zahirah Kuala Terengganu and Otorhinolaryngology Clinic of Hospital Universiti Sains Malaysia Kubang Kerian Kelantan commencing from June 2015 till May 2016. Study involves walk-in patient aged from 18-70 years old, who are seen in clinic from this two centres that are diagnosed with allergic rhinitis based on symptom and sign and had consented for skin prick test.Results: ANOVA test was applied to study the efficacy of isotonic and hypotonic nasal spray which includes TNSS, SNOT-22 and Modified Lund-Kennedy nasoendoscopic examination score. Only Modified Lund-Kennedy nasoendoscopic score showed significant difference between the two groups, F = -2.23, p = 0.026. Mann Whitney test was applied, median (IQR) for hypotonic spray =3.00(4.00) and isotonic spray 2.00(4.00). For inflammatory markers, effects of both method were analysed by using t-test. For IL-4, the difference between the mean isotonic and hypotonic nasal spray was not statistically significant (p = 0.337, 95% CI-0.91, 0.32). Same findings were demonstrated in eosinophil counts which showed no statistically different (p = 0.190, 95%CI -0.38, 0.08). Conclusions: There is not much difference on the efficacy between isotonic and hypotonic using clinical parameters and allergic inflammatory markers. The only significant findings in this study is by using the Modified Lund-Kennedy nasoendoscopic score which shows improvement with isotonic nasal spray. As a conclusion, isotonic INSs has a slightly superior efficacy than hypotonic INSs for treatment of AR in reducing the signs and symptoms.